Perlindungan Hukum bagi Pemegang Saham Publik Akibat Pengenaan Suspensi Perdagangan Saham Emiten Oleh Bursa Efek Indonesia - Amartya Kheista; Richard C. Adam (Syntax Literate, 2023)
The formulation of this study; a) What is the result of the suspension of trading shares of PT Falmaco Nonwoven Industri Tbk by the Indonesia Stock Exchange? This type of research belongs to normative legal research methods (normative juridical). Normative juridical research is legal research that puts law as a building system of norms. Normative legal research is also legal research conducted by researching using library materials or secondary data. In the event of suspension of PT Falmaco Nonwoven Industri Tbk due to late submission of financial statements and not paying fines, it can cause losses to shareholders, especially public shareholders who do not have control over a company. In the event of this loss, OJK, whose authority is supervision, inspection and protection, can be present as a legal step that can be taken by shareholders who are consumers in the financial services sector. OJK is present as a place to complain about things that are not reached.